Transparência ativa: estudo de caso do portal eletrônico do Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte - Oliveira, Acymara Catarina Zumba de (2021)
The Access to Information Law (Law No. 12,527/2011) is an important democratic advance as a result of the engagement of civil society and Brazil's adhesion to a global movement to encourage government transparency. This research carried out a diagnosis through the investigation of compliance with the LAI, specifically regarding active transparency on the website of the Federal Institute of Education, Science and Technology of Rio Grande do Norte - IFRN, through a survey of the essential elements for active transparency described in the LAI and in the Active Transparency Guide (GTA) for Bodies and Entities of the Federal Executive Power (BRASIL, 2019), the examination of the level of transparency of information on the IFRN institutional website with the application of a checklist built from the LAI and of the GTA's guidelines, and of the proposal of improvements for the adaptation of the institutional site to the rules of the right to information of public interest. The research used a qualitative and quantitative approach, descriptive, with the adoption of the inductive method and application of the bibliographic and documentary research technique. As a result of the diagnosis, it was found that the most deficient areas are “social participation” and “revenues and expenses”, which represent 20% of the thematic areas, classified with an insufficient level of transparency, which can significantly compromise the exercise of social control. The other areas, which represent 80% of the topics, were classified as having a partial transparency level. The observed gaps concern mainly failures in updating, integrity and authenticity of data. It is concluded that the active transparency of the IFRN on its website is partial. At the end, a model was built with parameters for the creation of an internal monitoring of the transparency of the entity's website.